2016
DOI: 10.1002/hyp.11059
|View full text |Cite
|
Sign up to set email alerts
|

Measuring and modeling vertical gradients in suspended sediments in the Solimões/Amazon River

Abstract: International audienceAccurately measuring sediment flux in large rivers remains a challenge due to the spatial and temporal cross-sectional variability of suspended sediment concentrations in conjunction with sampling procedures that fail to accurately quantify these differences. This study presents a field campaign methodology that can be used to improve the measurement of suspended sediment concentrations in the Amazon River or similarly large rivers. The turbidity signal and Rouse model are together used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 26 publications
(34 reference statements)
0
23
1
2
Order By: Relevance
“…In Lake Catalão, near the Solimões-Negro confluence, there is an increase in the number of species between January and February because of the high concentration of nutrients. The peak of suspended sediments in the Solimões River was observed during these months [8].…”
Section: Introductionmentioning
confidence: 90%
“…In Lake Catalão, near the Solimões-Negro confluence, there is an increase in the number of species between January and February because of the high concentration of nutrients. The peak of suspended sediments in the Solimões River was observed during these months [8].…”
Section: Introductionmentioning
confidence: 90%
“…The bulges represent secondary flow strength and direction, with the latter inferred from deviation of the primary flow from the gravity gradient for all cross-sections. The irregular distribution of velocity with depth ( Figure 11) also has implications for estimating suspended sediment flux in large deep rivers using functions such as the Rouse profile (Armijos et al, 2017). Thus, the presence of distinctive flow filaments can be used to infer the patterns of transverse flow and the distribution of bed shear stress.…”
Section: General Considerationsmentioning
confidence: 99%
“…Thus, the existence of strongly defined velocity filaments below the water surface is a clear indication of relatively strongly developed secondary transverse flow circulation with implications for shear stress distribution, bedload transport and bedrock erosion. The irregular distribution of velocity with depth ( Figure 11) also has implications for estimating suspended sediment flux in large deep rivers using functions such as the Rouse profile (Armijos et al, 2017).…”
Section: General Considerationsmentioning
confidence: 99%
“…Since 1995, the Environmental Research Observatory (SO-Hybam) and national institutes from the Amazon basin have been working together to build a discharge and suspended sediments dataset to understand the dynamics of water and sediment fluxes in different parts of the Amazon basin. The sediment flux was also estimated through indirect methods, such as turbidity and MODIS images (Espinoza Villar et al (2013), Armijos et al 2017, Espinoza-Villar et al (2018), or by using the spatial and temporal variation of gravitational fields from GRACE satellite data (Mouyen et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The Amazon River and its tributaries transport two well defined suspended sediment size fractions, which have different dynamics related to rainfall and discharge (Dunne et al 1998, Armijos et al 2017. Mertes and Meade (1985) showed that the bed forms are composed of dunes by 2 to 5 m in the Amazon River at Óbidos, and the particle size is between 125 to 500 μm in the Amazon River and its tributaries.…”
Section: Introductionmentioning
confidence: 99%